Analysis of methane-producing and metabolizing archaeal and bacterial communities in sediments of the northern South China Sea and coastal Mai Po Nature Reserve revealed by PCR amplification of mcrA and pmoA genes - Zhou, Zhichao; Chen, Jing; Cao, Huiluo; Han, Ping; Gu, Ji-Dong (Frontiers in Microbiology, 2015)
Communities of methanogens, anaerobic methanotrophic (ANME) archaea and aerobic methantrophic bacteria were compared by profiling mcrA and pmoA genes encoded by methyl-coenzyme M reductase alpha subunit and particulate methane monooxygenase alpha subunit, respectively, in sediments of northern South China Sea (nSCS) and Mai Po mangrove wetland. Community structures representing by mcrA gene based on 12 clone libraries from nSCS showed separate clusters indicating niche specificity, while, Methanomicrobiales, Methanosarcinales clade 1,2 and Methanomassiliicoccus like groups of methanogens were the most abundant constitutional parts in nSCS sediment samples . Novel clusters specific to the SCS were identified and the phylogeny of mcrA gene-harboring archaea was completely updated. Mai Po mangrove wetland surface layer exhibited lower diversity than subsurface, but similar community structures were shared in both layers. Quantitative PCR was used to detect mcrA gene abundance in all samples: similar abundance of mcrA gene in the surface layers of mangrove (3.4~3.9×106 copies per gram dry weight) and of intertidal mudflat (5.5~5.8×106 copies per gram dry weight) was observed, but higher abundance (6.9×106 to 1.02×108 copies per gram dry weight) was found in subsurface samples of both sediment types. Aerobic methanotrophic bacteria were more abundant in surface layers (6.7~11.1×105 copies per gram dry weight) than the subsurface layers (1.2~5.9×105copies per gram dry weight) based on pmoA gene. Mangrove surface layers harbored more abundant pmoA gene than intertidal, but fewer abundant pmoA genes in the subsurface layers. Meanwhile, it is also noted that in surface layers of all samples, more pmoA gene copies were detected than the subsurface layers. Reedbed rhizosphere exhibited the highest gene abundance of mcrA gene (8.51×108 copies per g dry weight) and pmoA gene (1.56×107 copies per g dry weight).